Multi Akad (Hybrid Contract) Inovasi Produk Lembaga Keuangan Syariah - Shofy Liza Nurul Arafah (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2018)
One of the parameters to assess whether a product meets sharia principles or not is to pay attention to the contracts and the various conditions used in the product. Products in Islamic finance activities, if against them are carried out by al-takyif al-fiqhi, some or even the majority of them contain several contracts. For example, in sharia credit card transactions there are ijarah, qardh and kafalah contracts, Islamic bonds contain at least mudharabah (or ijarah) and wakalah agreements, and sometimes with kafalah or wa'd, Islamic Swap contains several times the bargruq contract, bai ', wakalah, sharf and sometimes or always accompanied wa'ad. In every transaction, the contracts are carried out simultaneously or at least every contract contained in a product cannot be abandoned, because all of them are one entity. Such transactions are termed the multi contract (hybrid contract) which is now in the terminology of contemporary muamalat fiqh (fiqh al-mu'amalat al-maliyah al-mu'ashirah) called al-'uqud al-murakkabah.